Studying indicators of traditional architecture of Shiraz houses in order to provide a suitable model for contemporary housing design in order to use clean energy - tara heidari orojloo; afshin ghorbani param; faramarz hasanpour (تحقیقات کاربردی علوم جغرافیایی, 2023)
rchitecture is always influenced by various indicators, the most important of which are climatic and physical-spatial indicators. These indicators are well observed in traditional homes and have played an important role in the use of clean energy. In this study, the aim is to study the climatic and spatial indicators of traditional architecture of Shiraz houses in order to provide a suitable model for housing design in order to use clean energy. The research method is descriptive-analytical and based on data collection through a questionnaire. The validity of the instrument was confirmed by elite and the reliability was confirmed by Cronbach's alpha above 0.70. The statistical population of the research consists of 27089 experts, specialists and people familiar with the architecture of the building and a member of the Engineering System Organization of Fars Province. The number of samples according to Morgan table is 384 people. The result of one-sample t-test showed that all studied climatic and spatial variables including green space, proportions and composition of architectural elements, materials, sustainable architectural design of spaces, building orientation, organizing spaces, water use, maximum use of wind , The use of light and providing coolness with shade at a level less than 0.05 were significant and in terms of the statistical population, were in a good condition. Among the spatial and climatic variables of architecture, the most impact was related to the orientation variable with a value of 4.03 and then green space with an average of 3.85. The regression result showed that the most effective variables in the design of modern houses are related to the variable of proportions and composition of architectural elements with a value of 0.151 units, ie 15%.